Method for manufacturing electrode for secondary battery

By drying the electrode of the lithium secondary battery, the drying time is controlled by using a temperature higher than the melting point of the adhesive and the drying time is controlled, the problems of reduced electrode strength and productivity in the prior art are solved, and the adhesion and durability of the electrode are significantly improved.

CN119768925APending Publication Date: 2025-04-04LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380061368.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-25
Filing Date
2023-08-28
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, in order to prevent the decreasing of the crystallinity of the adhesive resin from being reduced, drying is necessary at a low temperature, resulting in difficulty in reducing the moisture residue, resulting in problems of reducing the electrode strength and productivity.

Method used

The drying was performed by a method where at least part of the drying temperature was higher than the melting point of the adhesive (170°C), and the total drying time was controlled to be less than 5 seconds. The roller-to-rolling process was dried, which significantly improved the adhesion between the electrode active material layer and the current collector.

Benefits of technology

It effectively reduces the amount of moisture residue in the electrode, reduces the crystallinity of the adhesive, significantly improves the adhesion and durability of the electrode, and improves the performance of the lithium secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768925A_ABST
    Figure CN119768925A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing an electrode for a secondary battery, the method effectively reducing the amount of residual moisture in the electrode while significantly improving the adhesion of the electrode. The method for preparing an electrode for a secondary battery comprises the steps of: preparing an electrode on which an electrode active material layer is formed; rolling the electrode; and drying the rolled electrode, wherein the drying is performed such that at least a partial section of the drying temperature is 170 DEG C to 210 DEG C (the melting point of the polyvinylidene fluoride (PVDF)-based binder resin (170 DEG C or more).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2022-0108709 filed on August 29, 2022 and Korean Patent Application No. 10-2023-0112358 filed on August 25, 2023, the disclosures of which are incorporated herein by reference. Technical Field

[0003] The present invention relates to a method for preparing an electrode for a secondary battery, and more particularly to a method for preparing an electrode for a secondary battery, which significantly improves the adhesion between an electrode active material layer and an electrode current collector by effectively reducing the amount of residual moisture in the electrode while minimizing the reduction in the crystallinity of a binder. Background Art

[0004] Recently, due to the rapid increase in the use of fossil fuels, the demand for the use of alternative or clean energy has increased. As part of this trend, power generation and power storage using electrochemistry are the most active areas of research.

[0005] A typical example of an electrochemical device using such electrochemical energy is a secondary battery, and there is a trend that its application field is increasingly expanding. In particular, in recent years, with the development of technology and the increase in demand for portable devices such as portable computers, mobile phones and cameras, the demand for high energy density secondary batteries, i.e., high capacity lithium secondary batteries, as energy sources has increased significantly.

[0006] Among these secondary batteries, a great deal of research has been conducted to develop lithium secondary batteries having a long cycle life and a low self-discharge rate while exhibiting high energy density and operating potential.

[0007] A lithium secondary battery is composed of a structure in which a chargeable and dischargeable electrode assembly of a positive electrode / separator / negative electrode structure is installed in a battery case, wherein the positive and negative electrodes are prepared as follows: a slurry in which an active material and a binder resin component are mixed is applied to one or both surfaces of a metal current collector to form an electrode active material layer, and then the electrode active material layer is dried and rolled.

[0008] In this case, in the past, in order to remove the moisture remaining in the electrode after rolling of the active material layer, the drying process is usually carried out at a low temperature where a conventional binder resin such as a polyvinylidene fluoride (PVDF) binder resin does not melt. If the drying process is carried out at a temperature higher than the melting point (170°C) of the polyvinylidene fluoride (PVDF) binder resin after rolling, the crystallinity is reduced due to the melting of the polyvinylidene fluoride (PVDF) binder resin, so the brittleness of the electrode is reduced, resulting in a reduction in electrode strength, leading to a problem of poor durability. In contrast, in the case of drying at a temperature below 170°C, a longer drying time is required to reduce the residual amount of moisture in the electrode to the desired level, so there is another problem of reduced productivity.

[0009] Therefore, it is necessary to develop a new method for preparing electrodes that can prevent the reduction of electrode strength during electrode preparation and improve adhesion by reducing the residual moisture in the electrode to a desired level. Summary of the invention

[0010] Technical issues

[0011] One aspect of the present invention provides a method for preparing an electrode for a secondary battery, wherein, when a drying process is performed after rolling, the drying process is performed in a manner that at least a portion of the drying temperature range is higher than the melting point (170° C.) of the binder and the total drying time is 5 seconds or less.

[0012] Technical Solution

[0013] According to one embodiment, the present invention provides a method for preparing an electrode for a secondary battery, comprising the following steps: preparing an electrode having an electrode active material layer formed on an electrode current collector; rolling the electrode; and drying the rolled electrode, wherein the drying is carried out in a manner in which at least part of the drying temperature ranges from 170°C to 210°C.

[0014] In the above method, the total drying time of the electrode after rolling can be 2 seconds to 5 seconds.

[0015] In addition, drying of the rolled electrode may be performed by a roll-to-roll process.

[0016] The drying of the rolled electrode is performed at a temperature above 130°C, and specifically may include the following steps: a first drying process at 130°C to 150°C; a second drying process at 150°C to 170°C; and a third drying process at 170°C to 210°C.

[0017] Beneficial effects

[0018] According to the method for preparing an electrode for a secondary battery of the present invention, when a drying process is performed after rolling, since the drying process is performed in a manner in which a partial range of the drying temperature is higher than the melting point (170°C) of the binder and the total drying time is less than 5 seconds, the residual moisture in the electrode can be effectively reduced while minimizing the reduction in the crystallinity of the binder. Therefore, the adhesion between the electrode active material layer and the electrode current collector can be significantly improved, thereby realizing a lithium secondary battery with improved durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings attached to the specification below illustrate preferred embodiments of the present invention and are used to enable the technical concept of the present invention to be further understood in conjunction with the detailed description of the present invention given below. Therefore, the present invention should not be interpreted solely based on the contents of these drawings.

[0020] Figure 1 This is a graph showing the evaluation results of the amount of residual water in the electrode of Experimental Example 1.

[0021] Figure 2 This is a graph showing the results of evaluating electrode adhesion according to Experimental Example 2. DETAILED DESCRIPTION

[0022] Hereinafter, the present invention will be described in more detail.

[0023] It should be understood that the terms (including technical and scientific terms) or words used in the specification and claims may be intended to have meanings understood by those skilled in the art. In addition, the terms defined in general dictionaries should not be interpreted abnormally or exaggeratedly unless clearly defined.

[0024] The terms used herein are only used for the purpose of describing specific example embodiments and are not intended to limit the present invention. In this specification, unless otherwise specified, terms in the singular may include plural forms. It should also be understood that when used in this specification, the terms "include" and / or "comprising" specify the presence of the components, but do not exclude the presence or addition of one or more other components.

[0025] In the present specification, unless specifically described to the contrary, in the case of stating that a component includes a certain component, it means that other components may be further included rather than excluding other components.

[0026] Hereinafter, the present invention will be described in more detail.

[0027] Method for preparing electrode for secondary battery

[0028] The method for preparing an electrode for a secondary battery of the present invention comprises the following steps:

[0029] (S1) preparing an electrode having an electrode active material layer formed on an electrode current collector;

[0030] (S2) rolling the electrode; and

[0031] (S3) drying the rolled electrode,

[0032] The drying is performed in a manner that at least a portion of the drying temperature is within a range of 170°C to 210°C.

[0033] In the past, in order to prevent the crystallinity of a binder resin such as a polyvinylidene fluoride (PVDF)-based binder resin from decreasing, a method was required in which an electrode in which an electrode active material layer is formed by coating one or both surfaces of a metal current collector with a slurry in which an active material and a binder resin are mixed is rolled, and then a drying process is performed at a low temperature (below 170° C.) at which the binder resin does not melt. However, in the case of drying at a low temperature, a long drying time is required to reduce the residual moisture in the electrode to a desired level, resulting in a problem of reduced productivity.

[0034] The inventors conducted extensive research to solve this problem and found that by performing the drying process after rolling with a partial range of drying temperature higher than the melting point (170°C) of the polyvinylidene fluoride (PVDF) type binder resin and a total drying time of less than 5 seconds, it is possible to minimize the reduction in the crystallinity of the binder resin while effectively reducing the amount of residual moisture in the electrode, thereby completing the present invention.

[0035] This will be explained in detail below.

[0036] (S1) Electrode preparation steps

[0037] The method for preparing an electrode for a secondary battery of the present invention may include the step of preparing an electrode having an electrode active material layer formed on an electrode current collector.

[0038] After preparing an electrode slurry composition by mixing or dispersing an electrode active material and a binder in a solvent, an electrode active material layer may be prepared by coating the electrode slurry composition on an electrode current collector and drying the coated electrode slurry composition.

[0039] In this case, the coating process of the electrode slurry composition on the electrode current collector can be carried out by methods known in the art, for example, the electrode slurry composition can be uniformly dispersed by using a doctor blade or by die casting, comma coating, screen printing and the like.

[0040] In addition, the drying process of the electrode paste composition coated on the electrode current collector can be carried out according to a known method. For example, it can be carried out by vacuum heat treatment within a specified temperature range or by heat treatment methods such as hot air spraying.

[0041] Furthermore, the temperature range of the drying process can be from 60°C to 130°C, particularly from 80°C to 130°C, and more particularly from 100°C to 130°C. In this case, when the temperature satisfies the above range, the moisture content in the electrode active material layer can be minimized, and since the volatile components contained during this process are sufficiently removed, deterioration of battery characteristics and occurrence of side reactions caused by these components during subsequent charge and discharge of the battery can be prevented. In particular, by carrying out the drying process at a temperature below 130°C, the migration phenomenon of the electrode active material or the binder constituting the electrode active material layer is suppressed. Therefore, the electrode active material or the binder is uniformly distributed in the electrode active material layer, and thus, an increase in the resistance of the secondary battery and a decrease in the adhesion between the current collector and the electrode active material layer can be improved.

[0042] The time required for the drying process can be from 5 minutes to 3 hours, particularly from 5 minutes to 20 minutes, and more particularly from 5 minutes to 10 minutes.

[0043] The electrode prepared by the method of the present invention can be a positive electrode and / or a negative electrode, and a positive electrode is particularly preferred.

[0044] Specifically, when the electrode prepared by the method of the present invention is a positive electrode, as the electrode active material, a lithium composite metal oxide capable of reversibly inserting and extracting lithium can be used, which contains lithium and at least one metal such as cobalt, manganese, nickel, or aluminum.

[0045] Specifically, the positive electrode active material can include lithium cobalt-based oxides (such as LiCoO 2 etc.), lithium manganese-based oxides (such as LiMnO 2 , LiMn 2 O 4 etc.), lithium nickel-based oxides (such as LiNiO 2 etc.), lithium nickel manganese-based oxides (such as LiNi 1-Y Mn Y O 2 (where 0 < Y < 1), LiMn 2-Z Ni Z O 4 (where 0 < Z < 2), etc.), lithium nickel cobalt-based oxides (such as LiNi 1-Y1 Co Y1 O 2 (where 0 < Y1 < 1), etc.), lithium manganese cobalt-based oxides (such as LiCo 1-Y2 MnY2 O 2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O 4 (where 0 < Z1 < 2), etc., lithium nickel manganese cobalt oxides (such as Li(Ni p Co q Mn r1 )O 2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1 and p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O 4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2 and p1 + q1 + r2 = 2), etc., or lithium nickel cobalt transition metal (M) oxides (such as Li(Ni p2 Co q2 Mn r3 M S2 )O 2 (where M is selected from the group consisting of aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg), Ti, and molybdenum (Mo), and p2, q2, r3, and S2 are the atomic fractions of each independent element, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < S2 < 1, and p2 + q2 + r3 + S2 = 1), etc.), and may include any one of them, or two or more of the compounds.

[0046] Among these materials, from the viewpoint of improving the capacity characteristics and stability of the battery, the positive electrode active material may include at least one selected from lithium cobalt oxides, lithium manganese oxides, lithium nickel manganese cobalt oxides, and lithium nickel cobalt transition metal (M) oxides.

[0047] Specifically, the positive electrode active material may include at least one selected from lithium nickel manganese cobalt oxides with a nickel content of 50 atm% or more, specifically 55 atm% or more, and / or lithium nickel cobalt transition metal (M) oxides with a nickel content of 50 atm% or more, specifically 55 atm% or more. Specifically, the positive electrode active material may include a lithium nickel cobalt transition metal (M) oxide represented by the following formula 1.

[0048] [Formula 1]

[0049] Li a Ni x Co y M 1 z M 2 w O 2

[0050] In Formula 1,

[0051] M 1 is manganese (Mn), aluminum (Al), or a combination thereof, and may preferably be Mn or Mn and Al.

[0052] M 2 is at least one selected from the group consisting of Al, zirconium (Zr), tungsten (W), titanium (Ti), magnesium (Mg), calcium (Ca), and strontium (Sr), may preferably be at least one selected from the group consisting of Al, Zr, yttrium (Y), Mg, and Ti, and more preferably is Al.

[0053] a represents the molar ratio of lithium in the lithium nickel cobalt transition metal (M) oxide, where a may satisfy 0.8 ≤ a ≤ 1.2, particularly 0.85 ≤ a ≤ 1.15, or more particularly 0.9 ≤ a ≤ 1.05. When the molar ratio of lithium satisfies the above range, the crystal structure of the lithium nickel cobalt transition metal (M) oxide can be formed stably.

[0054] x represents the molar ratio of nickel in all metals other than lithium in the lithium nickel cobalt transition metal (M) oxide, where x may satisfy 0.55 ≤ x < 1, particularly 0.55 ≤ a ≤ 0.95, more particularly 0.60 ≤ a ≤ 0.95, and even more particularly 0.8 ≤ x ≤ 0.95. When the molar ratio of nickel satisfies the above range, a high energy density can be exhibited to achieve a high capacity.

[0055] y represents the molar ratio of cobalt in all metals other than lithium in the lithium nickel cobalt transition metal (M) oxide, where y may satisfy 0 < y ≤ 0.3, preferably 0.001 < y < 0.3, particularly 0.025 ≤ b ≤ 0.20, more particularly 0.01 ≤ y < 0.20, and even more particularly 0.01 ≤ y < 0.15. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be achieved.

[0056] z represents the molar ratio of element M in all metals other than lithium in the lithium nickel cobalt transition metal (M) oxide 1 and z may satisfy 0 < z ≤ 0.3, preferably 0.001 < z ≤ 0.25, more preferably 0.01 ≤ z ≤ 0.20, more preferably 0.01 ≤ z ≤ 0.20, and more particularly 0.01 ≤ z ≤ 0.15. When the molar ratio of element M 1 satisfies the above range, the structural stability of the positive electrode active material is excellent.

[0057] w represents the molar ratio of element M in all metals other than lithium in the lithium nickel cobalt transition metal (M) oxide 2 and w may satisfy 0 < w ≤ 0.2, particularly 0 < w ≤ 0.1, and preferably 0 < w ≤ 0.05.

[0058] Specifically, in order to realize a high-capacity battery, the positive electrode active material may include a lithium composite transition metal oxide, such as Li(Ni 0.65 Mn 0.2 Co 0.15 ) 2 、Li(Ni 0.7 Mn 0.2 Co 0.1 ) 2 、Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 、Li(Ni 0.8 Co 0.15 Al 0.05 ) 2 、Li(Ni 0.86 Mn 0.07 Co 0.05 Al 0.02 ) 2 Or Li(Ni 0.90 Mn 0.05 Co 0.05 ) 2 and may preferably contain Li(Ni) containing 80 mol% or more of nickel (Ni) based on the total molar number of transition metals. 0.86 Mn 0.07 Co 0.05 Al 0.02 ) 2 .

[0059] As required, the positive electrode active material of the present invention may further include a coating layer on the surface of the lithium nickel oxide particles, wherein the coating layer contains at least one coating element selected from the group consisting of Al, Ti, W, boron (B), fluorine (F), phosphorus (P), Mg, Ni, cobalt (Co), Fe, Cr, V, copper (Cu), Ca, zinc (Zn), Zr, niobium (Nb), molybdenum (Mo), Sr, antimony (Sb), bismuth (Bi), silicon (Si) and sulfur (S). Preferably, the coating element may be Al, B, Co or a combination thereof.

[0060] When a coating layer exists on the surface of the lithium nickel oxide particles, the coating layer inhibits contact between the non-aqueous electrolyte and the lithium composite transition metal oxide, resulting in reduced gas generation or transition metal dissolution caused by side reactions with the non-aqueous electrolyte.

[0061] Based on the total weight of the solids in the positive electrode slurry composition, the content of the positive electrode active material may be 80 wt % to 99 wt %, specifically 90 wt % to 99 wt %. When the amount of the positive electrode active material satisfies the above range, the battery capacity of the positive electrode can be increased by ensuring sufficient positive electrode energy density.

[0062] The binder is a component that improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector, wherein the binder is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the solids in the positive electrode slurry composition. An example of the binder may be a polyvinylidene fluoride (PVDF)-based binder resin having a melting point of 170° C. or more.

[0063] According to one embodiment of the present invention, the content of the binder in the solid content of the positive electrode slurry composition may be 0.5 wt % to 3.5 wt %, specifically 0.5 wt % to 3.0 wt %, and more specifically 0.5 wt % to 1.5 wt %.

[0064] The positive electrode slurry composition may be prepared by mixing or dispersing a conductive agent and a dispersant in addition to the positive electrode active material and the binder in a solvent as needed.

[0065] There is no particular limitation on the conductive agent as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, the following can be used: carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black; graphite powder, such as natural graphite, artificial graphite or graphite with a well-developed crystal structure; conductive fibers, such as carbon fibers or metal fibers; fluorocarbon powder; metal powder, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0066] In the solids of the positive electrode slurry composition, the content of the conductive agent may be 1.5 wt % or less, particularly 0.5 wt % to 1.0 wt %, and more particularly 0.6 wt % to 1.0 wt %. When the amount of the conductive agent in the solids of the positive electrode slurry composition satisfies the above range, the conductivity of the positive electrode can be improved by ensuring a positive electrode conductive network.

[0067] The dispersant inhibits the phenomenon of excessive aggregation of the positive electrode active material in the positive electrode slurry composition, so that the positive electrode active material is effectively dispersed in the prepared positive electrode active material layer. The dispersant may include a hydrogenated nitrile copolymer, specifically, a copolymer comprising a structural unit derived from an α, β-unsaturated nitrile and a structural unit derived from a hydrogenated conjugated diene, or a copolymer comprising a structural unit derived from an α, β-unsaturated nitrile, a structural unit derived from a conjugated diene, and a structural unit derived from a hydrogenated conjugated diene. As an α, β-unsaturated nitrile monomer, for example, acrylonitrile or methacrylonitrile may be used, or one or a mixture of two or more thereof may be used alone. As a conjugated diene monomer, for example, a conjugated diene monomer having 4 to 6 carbon atoms, such as 1,3-butadiene, isoprene, 2,3-methylbutadiene, etc., may be used, and one or a mixture of two or more thereof may be used alone.

[0068] More specifically, the hydrogenated nitrile copolymer may be hydrogenated nitrile butadiene rubber (H-NBR).

[0069] In the solids of the positive electrode slurry composition, the content of the dispersant may be 1.5 wt % or less, particularly 1.2 wt % or less, and more particularly 0.1 wt % to 1.0 wt %. When the amount of the dispersant satisfies the above range, the positive electrode conductive network can be improved by inhibiting the aggregation of the conductive agent in the solids of the positive electrode slurry composition.

[0070] In the case where the electrode prepared by the method of the present invention is a positive electrode, the electrode current collector is not particularly limited as long as it is a positive electrode current collector having conductivity and not causing adverse chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used.

[0071] Specifically, the positive electrode current collector may have a thickness of 3 μm to 500 μm, and microscopic concavoconvexities may be formed on the surface of the positive electrode current collector to improve adhesion with the positive electrode active material layer. For example, the positive electrode current collector may be used in various shapes such as a film, a sheet, a foil, a net, a porous body, a foam body, a non-woven fabric body, etc.

[0072] In addition, the solvent used in the preparation process of the electrode slurry composition may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and its amount may be such that the desired viscosity is obtained when the positive electrode active material and the optional binder and the conductive agent are included. For example, the content of the solvent may be such that the concentration of the solids in the active material slurry containing the positive electrode active material and the optional binder and the conductive agent is 10 wt % to 90 wt %, preferably 30 wt % to 80 wt %.

[0073] (S2) Rolling Electrode Process

[0074] The method for preparing an electrode for a secondary battery of the present invention may include a step of performing a roll-pressing treatment on the dried electrode.

[0075] The rolling process can be performed by a rolling pressing method, but is not limited thereto. For example, the rolling process can also be performed by a hot pressing method.

[0076] Before the rolling process, the porosity of the dried electrode active material layer may be 55% or less, particularly 35% to 55%, and more particularly 40% to 55%. When the porosity of the dried electrode active material layer satisfies the above range, the rolling process of the dried electrode active material layer is easy, and thus it is desirable.

[0077] The electrode active material layer after drying may be subjected to a rolling process once or more, particularly 2 to 5 times, more particularly 3 to 5 times. In this case, the rolling process may be performed until the rolling ratio of the electrode active material layer exceeds a specific value. For example, the rolling ratio of the electrode active material layer after the rolling process may be 10% or more, particularly 10% to 17%, more particularly 10% to 15%. In the case where the rolling ratio of the electrode active material layer after the rolling process satisfies the above range, as long as the electrode active material layer is not peeled off, the number of rolling times in the second rolling process can be minimized by sufficiently rolling the electrode active material.

[0078] In addition, the thickness change rate after the rolling process can be less than 3.5%, particularly 0.1% to 3.5%, and more particularly 0.5% to 3.5%. When the thickness of the electrode active material layer after the rolling process meets the above range, a high-density electrode can be prepared while preventing the peeling of the electrode active material layer. When the thickness change rate in the rolling process is greater than 3.5%, the electrode active material layer may be peeled off from the electrode current collector due to the fracture of the low-strength portion of the electrode active material layer (for example, a portion or edge portion with a thickness thinner than the average thickness).

[0079] In addition, after the rolling process, the porosity of the electrode active material layer may be 20% to 36%, particularly 20% to 34%, and more particularly 25% to 34%. The porosity of the electrode active material layer after the rolling process is related to the thickness of the electrode active material layer after the rolling process. Therefore, when the porosity of the electrode active material layer after the rolling process satisfies the above range, a high-density positive electrode can be prepared while preventing the electrode active material layer from peeling off.

[0080] (S3) Step of drying the rolled electrode

[0081] The method for preparing an electrode for a secondary battery of the present invention may include a step of drying the rolled electrode.

[0082] In this case, drying is performed at a temperature of 130°C or higher, but at least a portion of the drying temperature may be higher than the melting point (170°C) of the polyvinylidene fluoride (PVDF)-based binder resin, that is, 170°C to 210°C.

[0083] The drying process may be performed by a roll-to-roll process method, but is not limited thereto.

[0084] Specifically, the drying of the rolled electrode can be performed in three drying processes while the temperature is raised in sequence. Specifically, the drying of the rolled electrode can include the following steps: a first drying process at 130°C to 150°C; a second drying process at 150°C to 170°C; and a third drying process at 170°C to 210°C.

[0085] As described above, when the drying process after rolling is carried out in the method of the present invention, the drying process is carried out in a manner that the drying temperature is gradually increased from 130°C to 210°C and a partial range of the drying temperature is 170°C to 210°C. This allows the active material or binder in the electrode layer to be uniformly heated. Therefore, the reduction in the crystallinity of the polyvinylidene fluoride (PVDF)-based binder resin can be minimized while effectively reducing the residual moisture in the electrode, thereby preventing the resistance of the secondary battery from increasing, further improving the adhesion between the electrode active material layer and the current collector, and achieving the effect of improving productivity.

[0086] In the case of performing a drying process while lowering the temperature from a high temperature to a low temperature, for example, after performing the first process at about 180°C to 170°C close to the melting point (170°C) of the polyvinylidene fluoride (PVDF) type binder resin, the temperature is gradually lowered to 130°C. In the case of performing a drying process, the imbalance of the physical properties of the electrode becomes larger due to the irregular growth of the crystals of the partially melted polyvinylidene fluoride (PVDF) binder resin, and the possibility of increasing the phenomenon of electrode brittleness due to the irregularly grown crystals is high. Therefore, as in the present invention, by performing a drying process so that the temperature is successively increased from 130°C and the drying temperature of the partial drying process is higher than the melting point (170°C) of the polyvinylidene fluoride (PVDF) type binder resin, the polyvinylidene fluoride (PVDF) type binder resin can be uniformly dissolved. Therefore, even if a room temperature (rapid) cooling process is performed as a subsequent process, the overall crystal size of the binder resin is uniform, so that an electrode with similar overall physical properties can be prepared. In particular, the small crystals formed by the rapid cooling process can improve the strength (toughness) of the electrode.

[0087] The total drying time of the rolled electrode may be 5 seconds or less, specifically, 2 seconds to 5 seconds.

[0088] When the drying time meets the above range, the residual amount of moisture in the electrode can be effectively reduced while minimizing the reduction of crystallinity. If the drying time is greater than the above range, due to the reduction of the crystallinity of the polyvinylidene fluoride (PVDF) - based binder, the physical properties (adhesion, toughness) of the electrode change compared with those before drying, which may change the thickness or area of the electrode.

[0089] The positive electrode can be suitably used as the positive electrode of a lithium secondary battery.

[0090] Taking the lithium secondary battery including the above positive electrode as an example for illustration.

[0091] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode disposed facing the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the above positive electrode is used as the positive electrode. In addition, the lithium secondary battery may further include a case that houses an electrode assembly in which the positive electrode, the separator, and the negative electrode are stacked in sequence.

[0092] Next, each component of the lithium secondary battery of the present invention will be described in more detail.

[0093] The negative electrode may be configured with a structure in which a negative electrode active material layer is formed on one surface or both surfaces of a long - sheet - shaped negative electrode current collector. The negative electrode active material layer may contain a negative electrode active material and may optionally further contain a conductive agent and / or a binder.

[0094] Specifically, a compound capable of reversibly inserting and extracting lithium can be used as the negative electrode active material. Specific examples of the negative electrode active material may be: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; silicon - based materials such as Si, Si - Me alloy (where Me is at least one selected from the group consisting of Al, tin (Sn), Mg, Cu, Fe, lead (Pb), Zn, Mn, Cr, Ti, and Ni), SiO y (where 0 < y < 2) and Si - C composite materials; lithium metal thin films; or metal materials capable of alloying with lithium such as Sn and Al, and any one of them or a mixture of two or more of them can be used.

[0095] Preferably, the negative electrode active material of the present invention may contain at least one of a carbon - based negative electrode active material and a silicon - based negative electrode active material.

[0096] The silicon - based negative electrode active material may be Si, Si - Me alloy (where Me is at least one selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), SiO y (where 0 < y < 2), Si - C composite, or a combination thereof, and may preferably be SiO y(where 0 < y < 2). Since the silicon-based negative electrode active material has a high theoretical capacity, the capacity characteristics can be improved when the silicon-based negative electrode active material is included.

[0097] The silicon-based negative electrode active material may be doped with M b metal. In this case, M b metal may be a Group 1 metal element or a Group 2 metal element, and specifically may be lithium (Li) or Mg. Specifically, the silicon-based negative electrode active material may be Si, SiO b (where 0 < y < 2), and Si-C composite doped with M y metal. For the metal-doped silicon-based negative electrode active material, the capacity of the active material is slightly reduced due to the doping element. However, due to its high efficiency, a high energy density can be achieved.

[0098] In addition, the silicon-based negative electrode active material may also include a carbon coating layer on the surface of the particles. In this case, based on the total weight of the silicon-based negative electrode active material, the carbon coating amount may be 20% by weight or less, preferably 1% to 20% by weight.

[0099] The conductive agent is a component for further improving the conductivity of the negative electrode active material. Among them, based on the total weight of the solids in the negative electrode active material layer, the addition amount of the conductive agent may be 1% to 20% by weight. Any conductive agent can be used without particular limitation as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, the following conductive materials can be used, such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking carbon black; conductive fibers, such as carbon fibers or metal fibers; conductive powders, such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers, such as zinc oxide whiskers, potassium titanate whiskers, etc.; conductive metal oxides, such as titanium oxide, etc.; or polyphenylene derivatives.

[0100] The binder is a component that helps the binding between the conductive agent, the active material, and the current collector. Among them, based on the total weight of the solids in the negative electrode active material layer, the usual addition amount of the binder may be 1% to 30% by weight. Examples of the binder may be: fluororesin binders containing polyvinylidene fluoride or polytetrafluoroethylene; rubber binders containing styrene-butadiene rubber, acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose binders containing carboxymethyl cellulose, starch, hydroxypropyl cellulose, or regenerated cellulose; polyol binders containing polyvinyl alcohol; polyolefin binders containing polyethylene or polypropylene; polyimide binders; polyester binders; and silane binders.

[0101] The negative electrode can be prepared according to a method for preparing a negative electrode known in the art. For example, the negative electrode can be prepared by the following method: a method of preparing a negative electrode active material slurry by dissolving or dispersing a negative electrode active material and an optional binder and a conductive agent in a solvent, and coating the negative electrode active material slurry on a negative electrode current collector, rolling and drying to form a negative electrode active material layer; or a method of casting a negative electrode active material layer on a separate support, and then laminating a film separated from the support on a negative electrode current collector.

[0102] The thickness of the negative electrode collector is generally 3 μm to 500 μm. The negative electrode collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel or aluminum-cadmium alloy surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, similar to the positive electrode collector, the negative electrode collector may have fine surface irregularities to improve the bonding strength with the negative electrode active material, and the negative electrode collector may include various shapes, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0103] The solvent may include water or an organic solvent such as NMP and alcohol, and its amount may be such that a desired viscosity is obtained when the negative electrode active material and optional binder and conductive agent are included. For example, the content of the solvent may be such that the concentration of solids in the active material slurry containing the negative electrode active material and optional binder and conductive agent is 50 wt % to 75 wt %, preferably 50 wt % to 65 wt %.

[0104] The separator separates the negative electrode and the positive electrode and provides a path for the movement of lithium ions. As the separator, any separator can be used without particular limitation as long as it is commonly used in lithium secondary batteries. In particular, a separator having high moisture retention capacity for non-aqueous electrolytes and low resistance to the transfer of non-aqueous electrolyte ions is preferred.

[0105] Specifically, as a separator, a porous polymer film can be used, for example, a porous polymer film prepared from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, an ethylene / methacrylate copolymer, or a laminated structure having more than two layers. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed of a high melting point glass fiber or a polyethylene terephthalate fiber. In addition, in order to ensure heat resistance or mechanical strength, a coated separator including a ceramic component or a polymer material can be used, and a separator having a monolayer or multilayer structure can be optionally used.

[0106] As the electrolyte used in the present invention, various electrolytes that can be used for lithium secondary batteries, such as organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes or molten inorganic electrolytes can be used, and their types are not particularly limited.

[0107] In addition, the electrolyte may include an organic solvent and a lithium salt.

[0108] As the organic solvent, any organic solvent can be used without particular limitation, as long as it can be used as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, as the organic solvent, carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC) can be used; ester solvents such as methyl acetate and ethyl acetate; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; alcohol solvents such as ethanol and isopropanol; amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or cyclopentane sulfone can be used. Among these solvents, carbonate solvents are preferred, and more preferably a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant and low viscosity straight-chain carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) which can improve the charge and discharge performance of the battery.

[0109] The lithium salt may be used without particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 , LiCl, LiII or LiB(C2 O 4 ) 2 As a lithium salt. The lithium salt may be used in a concentration of 0.1 M to 5.0 M, preferably 0.1 M to 3.0 M. If the concentration of the lithium salt is included in the above range, the electrolyte may have appropriate conductivity and viscosity, and thus excellent electrolyte performance may be obtained, and lithium ions may be efficiently moved.

[0110] In order to improve the life characteristics of the battery, suppress the reduction of the battery capacity and improve the discharge capacity of the battery, the electrolyte can further contain additives. For example, as additives, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol or aluminum chloride can be used alone or in combination, but are not limited to this. Based on the gross weight of the electrolyte, the content of the additive can be 0.1 weight % to 10 weight %, preferably 0.1 weight % to 5 weight %.

[0111] As described above, the lithium secondary battery of the present invention can be suitably used in portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0112] Hereinafter, the present invention will be described in more detail according to examples. However, the following examples are only for illustrating the present invention, and the scope of the present invention is not limited thereto.

[0113] [Example]

[0114] Example 1

[0115] (1) Preparation of positive electrode slurry composition

[0116] By 0.86 Mn 0.07 Co 0.05 Al 0.02 ) 2 ), carbon nanotubes as a conductive agent and polyvinylidene fluoride (PVDF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 97:1:2 to prepare a positive electrode slurry composition (solid content: 70 wt %).

[0117] (2) Cathode preparation

[0118] The positive electrode slurry composition prepared above was coated on an aluminum thin film current collector with a thickness of 15 μm, and then dried at 130° C. for 1 minute to form a positive electrode active material layer (thickness 218 μm).

[0119] Next, after the dried positive electrode active material layer was roll-pressed until the thickness of the positive electrode active material layer was 164 μm, the following steps were performed in sequence: a first drying process at 130° C., a second drying process at 150° C., and a third drying process at 170° C., thereby preparing a positive electrode. The total drying time was within 5 seconds.

[0120] Example 2

[0121] The positive electrode slurry composition prepared in Example 1 was coated on a 15 μm thick aluminum thin film current collector and then dried at 130° C. for 1 minute to form a positive electrode active material layer (thickness: 218 μm).

[0122] Next, after the dried positive electrode active material layer was roll-pressed until the thickness of the positive electrode active material layer was 164 μm, the following steps were performed in sequence: a first drying process at 150° C., a second drying process at 170° C., and a third drying process at 190° C., thereby preparing a positive electrode. The total drying time was within 5 seconds.

[0123] Example 3

[0124] The positive electrode slurry composition prepared in Example 1 was coated on a 15 μm thick aluminum thin film current collector and then dried at 130° C. for 1 minute to form a positive electrode active material layer (thickness: 218 μm).

[0125] Next, after the dried positive electrode active material layer was roll-pressed until the thickness of the positive electrode active material layer was 164 μm, the following steps were performed in sequence: a first drying process at 150° C., a second drying process at 170° C., and a third drying process at 210° C., thereby preparing a positive electrode. The total drying time was within 5 seconds.

[0126] Comparative Example 1

[0127] The positive electrode slurry composition prepared in Example 1 was coated on a 15 μm thick aluminum thin film current collector and then dried at 130° C. for 1 minute to form a positive electrode active material layer (thickness: 218 μm).

[0128] Next, after the dried positive electrode active material layer was roll-pressed until the thickness of the positive electrode active material layer became 164 μm, the positive electrode was prepared by sequentially performing the following steps: a first drying process at 110° C. and a second drying process at 130° C. The total drying time was within 5 seconds.

[0129] Comparative Example 2

[0130] The positive electrode slurry composition prepared in Example 1 was coated on a 15 μm thick aluminum thin film current collector and then dried at 130° C. for 1 minute to form a positive electrode active material layer (thickness: 218 μm).

[0131] Next, the dried positive electrode active material layer was subjected to a roll pressing process until the thickness of the positive electrode active material layer reached 164 μm, and then a drying process was performed at 130° C. for 5 seconds.

[0132] [Experimental example]

[0133] Experimental Example 1. Determination of Residual Water Content in the Positive Electrode Active Material Layer

[0134] The solvent (water) content of each of the positive electrodes prepared in Examples 1 to 3 and the positive electrodes prepared in Comparative Examples 1 and 2 was determined by Karl Fischer titration. Specifically, the positive electrodes prepared in Examples 1 to 3 and the positive electrode prepared in Comparative Example 1 were each cut into small pieces of 5 cm×5 cm in a glove box filled with argon. The cut positive electrode with a size of 5 cm×5 cm was weighed in a sample bottle. Then, the weighed positive electrode was measured repeatedly 3 times using a Karl Fischer coulometric moisture meter (831kF coulometer, Metrohm, Switzerland), and the average value was calculated. The results are shown below. Figure 1 middle.

[0135] Reference Figure 1 It can be confirmed that the residual moisture content in the positive electrodes prepared in Examples 1 to 3 of the present invention is significantly reduced compared with the positive electrodes prepared in Comparative Examples 1 and 2.

[0136] Experimental Example 2. Evaluation of Adhesion to Electrode Current Collector

[0137] The positive electrodes prepared in Examples 1 to 3 and the positive electrodes prepared in Comparative Examples 1 and 2 were cut into 20 mm wide / 125 mm long pieces and fixed on a glass slide, and then the current collector was peeled off and the 90° peel strength was measured. The measurement was repeated 3 times and the average value was calculated. The results are shown in Figure 2 .

[0138] Reference Figure 2 It can be confirmed that, compared with the positive electrodes prepared in Comparative Examples 1 and 2, the adhesion of the positive electrodes prepared in Examples 1 to 3 of the present invention is significantly increased.

Claims

1. A method for preparing an electrode for a secondary battery, the method comprising the following steps: preparing an electrode having an electrode active material layer formed on an electrode current collector; Rolling the electrode; as well as Dry the rolled electrode. The drying is performed in a manner that at least a portion of the drying temperature is in a range of 170°C to 210°C.

2. The method according to claim 1, wherein: The total drying time of the rolled electrode is 2 to 5 seconds.

3. The method according to claim 1, wherein: The drying of the rolled electrode is performed by a roll-to-roll process.

4. The method according to claim 1, wherein: The electrode after rolling is dried at a temperature of 130° C. or higher.

5. The method according to claim 1, wherein: In the drying of the rolled electrode, the following steps are performed in sequence: a first drying process at 130°C to 150°C; a second drying process at 150°C to 170°C; and a third drying process at 170°C to 210°C.

6. The method according to claim 1, wherein: The electrode active material layer includes an electrode active material and a binder, and The electrode active material includes a positive electrode active material or a negative electrode active material.

7. The method according to claim 6, wherein: The binder includes a polyvinylidene fluoride-based resin.

8. The method according to claim 6, wherein: The electrode active material is a positive electrode active material.

9. The method according to claim 8, wherein: The positive electrode active material includes a lithium nickel cobalt transition metal (M) oxide represented by Formula 1: [Formula 1] Li a Ni x Co y M 1 z M 2 w O2 Among them, in Formula 1, M 1 is manganese (Mn), aluminum (Al) or a combination thereof, M 2 is at least one selected from the group consisting of Al, zirconium (Zr), tungsten (W), titanium (Ti), magnesium (Mg), calcium (Ca) and strontium (Sr), and 0.8 ≤ a ≤ 1.2, 0.55 ≤ x < 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3 and 0 < w ≤ 0.

2.

10. The method according to claim 9, wherein: The positive electrode active material has a nickel (Ni) content of 55% or more.

11. The method according to claim 1, wherein: The electrode is a positive electrode.

Citation Information

Patent Citations

  • Thermal conductive structure and electronic device

    KR1020220108709A

  • Multi-joint robot for welding

    KR1020230112358A